2021
DOI: 10.21037/atm-20-6207
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G2 promotes the formation of smooth muscle cells derived foam cells in atherosclerosis via PP2A/NF-κB/LOX-1 pathway

Abstract: Background: To investigate the role and underlying mechanism of cyclin G2 (G2-type cyclin) in the formation of vascular smooth muscle cells (VSMCs) derived foam cells. Methods:The levels of α-SMA (alpha-SM-actin), p-NF-κB (phosphorylation nuclear transcription factors kappa B), and LOX-1 (lectin-like oxidized low-density lipoprotein receptor-1) were measured by immunohistochemistry and western blotting. The mouse aortic root smooth muscle cell line MOVAS was transfected to over-express cyclin G2, which were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Protein phosphatase 2 phosphatase activator (PP2A) was previously shown to attenuate IFN-γ-induced STAT1 phosphorylation [13][14][15]; cyclin G2 interacts with PP2Ac to affect its function [37][38][39]. Accordingly, we examined whether PP2Ac was involved in the change in STAT1 nuclear content in macrophages after cyclin G2 knockdown.…”
Section: Stat1 Nuclear Translocation Mediated By Cyclin G2 Is Depende...mentioning
confidence: 99%
“…Protein phosphatase 2 phosphatase activator (PP2A) was previously shown to attenuate IFN-γ-induced STAT1 phosphorylation [13][14][15]; cyclin G2 interacts with PP2Ac to affect its function [37][38][39]. Accordingly, we examined whether PP2Ac was involved in the change in STAT1 nuclear content in macrophages after cyclin G2 knockdown.…”
Section: Stat1 Nuclear Translocation Mediated By Cyclin G2 Is Depende...mentioning
confidence: 99%
“…During the recruitment of white blood cells from the bloodstream to the intima of the vessel, Icam-1 primarily acts as an integrin receptor, whereas MCP-1 helps recruit monocytes [ 35 ]. The pro-inflammatory cytokines induce the expression of ICAM-1, MCP-1, LOX-1, and 5-LOX and convert macrophages and smooth muscle cells into foam cells to form atherosclerotic plaques [ 39 ]. Additionally, these pro-inflammatory processes mediated by OX-LDL and LOX1 are thought to result in enlargement of lipid cores, rupture of lesions, and instability of arterial thrombosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Chen et al showed that PP2A deactivates eNOS by removing S1177 residue phosphorylation and reduces NO bioavailability ( 23 ). Zhang et al reported that PP2A activation using a PP2A activator DT-061 reduced the uptake and accumulation of lipids in mouse aortic vascular smooth muscle cells ( 24 ). Campbell et al and Yang found that decreased PP2A activity enhances the migration of vascular smooth muscle cells ( 25 , 34 ).…”
Section: Discussionmentioning
confidence: 99%